PERANAN MUSEUM DALAM BIDANG KESENIRUPAAN - Sunaryo Sunaryo (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
Museum is one of public facilities preserving a collection of cultural heritage from the past to the present time which can be also used for learning purposes. This research aims at knowing and describing how a museum can be benefitted as a learning resource. The research was conducted at Museum Fatahillah in Kota Tua, Jakarta. This museum contains a number of prehistoric collection. Three questions were raised in this research: how the Museum organizes the art works, how is the quality and the quantity of the works on the display, and how the museum can be used as a learning resource. The data was collected by using observation, interview, document study techniques and was analyzed qualitatively to answer the research questions. The research findings indicate the Museum has a variety of art collection well organized on display, the collection has cultural value and can be benefitted as a learning resource.